2004
DOI: 10.1271/bbb.68.671
|View full text |Cite
|
Sign up to set email alerts
|

Retarding Effects of Cyclodextrins on the Decomposition of Organic Isothiocyanates in an Aqueous Solution

Abstract: One-and two-dimensional 1 H nuclear magnetic resonance ( 1 H NMR) spectra were measured in order to estimate the dissociation constants (K diss ) and molecular geometries of cyclodextrin (CD) with three organic isothiocyanates (ITC), allyl-ITC, 3-butenyl-ITC, and 4-pentenyl-ITC, in an aqueous solution (pH 5.0, I c ¼ 0:75 M). In every ITC, the K diss values decreased in the order of -CD > -CD > -CD, and the three rod-like linear molecules of ITCs were accommodated with the best fit into the smallest cavity of -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…4). The peaks for AITC were observed at around 4.2, 5.3, and 5.9 ppm corresponding to the protons of AITC [34]. The stoichiometry of AITC and ␤-CD-IC in PVA/AITC/␤-CD-IC-NF was determined as 0.68:1.00 (AITC:␤-CD) by integrating the peak ratio of the characteristic chemical shifts of AITC (5.3 ppm) and ␤-CD (5.7 ppm).…”
Section: Aitc Content In Nanofibersmentioning
confidence: 99%
“…4). The peaks for AITC were observed at around 4.2, 5.3, and 5.9 ppm corresponding to the protons of AITC [34]. The stoichiometry of AITC and ␤-CD-IC in PVA/AITC/␤-CD-IC-NF was determined as 0.68:1.00 (AITC:␤-CD) by integrating the peak ratio of the characteristic chemical shifts of AITC (5.3 ppm) and ␤-CD (5.7 ppm).…”
Section: Aitc Content In Nanofibersmentioning
confidence: 99%
“…Many physicochemical methods were applied to investigate the complexation reaction between CDs and guest molecule, including phase solubility measurements , UV–Vis , fluorescence , circular dichroism , and NMR spectroscopy. Furthermore, many separation‐based methods such as HPLC and CE were also used to study the host–guest interaction.…”
Section: Introductionmentioning
confidence: 99%
“…aCD provided better stabilization of MTBI than did bCD and gCD. Ohta et al (32) have reported the isothiocyanate group of AITC is located close to the secondary hydrogen group, and the hydrophobic allyl group is located within the hydrophobic cavity of aCD. We speculate that MTBI forms a complex with aCD through interactions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…12), similar to what has been reported for AITC. (32) The reactive site of MTBI can be protected from nucleophilic attack of water by the steric hindrance of the aCD torus. In addition, by forming the inclusion complex with aCD, MTBI in MTBI-aCD could be stably stored for a long time.…”
Section: Discussionmentioning
confidence: 99%